2011
DOI: 10.1117/12.873074
|View full text |Cite
|
Sign up to set email alerts
|

Autoclaveable miniaturized video endoscopes with simplified flip-chip assembly

Abstract: Miniaturized video endoscopes with an imager located at the distal end and a simplified opto-mechanical layout are presented. They are based on a CMOS imager with 650 x 650 pixels of 2.8 ?m pitch and provide straight view with 75 ° and 110 ° field of view at f/4.3. They have an outer diameter of 3 mm including the shell and a length of approx. 8 mm. The optics consist of polymer lenses in combination with a GRIN and a dispensed lens. Using a simple flip chip assembly, optical axis alignment better than 10 ?m a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It's reported that the sensor can reach a resolution up to 190 line pairs/mm with pixel dimensions of 2.8 µm and 422 500 pixels in an image diameter of 2.6 mm in a research from Fraunhofer IOF, especially the camera module has only 3 mm in diameter and 6.4 mm in length 3 . Figure 2: Structure example of the chip-on-tip 3 Although the optical system in the Figure 2 is made from polymer, glass lenses can have a stronger performance in such as ophthalmology and robotic endoscopy procedures 4 . Moreover, the optical surfaces are tended to be aspherical surfaces in order to achieve the specified optical performance in a structure as compact as possible in the endoscope 3,4 .…”
Section: Introduction 11 Chip-on-tip Endoscopementioning
confidence: 99%
See 1 more Smart Citation
“…It's reported that the sensor can reach a resolution up to 190 line pairs/mm with pixel dimensions of 2.8 µm and 422 500 pixels in an image diameter of 2.6 mm in a research from Fraunhofer IOF, especially the camera module has only 3 mm in diameter and 6.4 mm in length 3 . Figure 2: Structure example of the chip-on-tip 3 Although the optical system in the Figure 2 is made from polymer, glass lenses can have a stronger performance in such as ophthalmology and robotic endoscopy procedures 4 . Moreover, the optical surfaces are tended to be aspherical surfaces in order to achieve the specified optical performance in a structure as compact as possible in the endoscope 3,4 .…”
Section: Introduction 11 Chip-on-tip Endoscopementioning
confidence: 99%
“…Figure 2: Structure example of the chip-on-tip 3 Although the optical system in the Figure 2 is made from polymer, glass lenses can have a stronger performance in such as ophthalmology and robotic endoscopy procedures 4 . Moreover, the optical surfaces are tended to be aspherical surfaces in order to achieve the specified optical performance in a structure as compact as possible in the endoscope 3,4 .…”
Section: Introduction 11 Chip-on-tip Endoscopementioning
confidence: 99%